Developing trends of initial nursing education in China from 2006 to 2017: A descriptive analysis based on national-level data. (March 2022) - Fu, Xue; You, Liming; Liu, Xu; Zheng, Jing; Gubrud-Howe, Paula; Liu, Jiali; Li, Mengqi; Wan, Lihong
Abstract: Introduction: There is currently a global nurse shortage. Initial nursing education is the primary preparation for a robust nursing workforce that must be strengthened. Objectives: To describe the developing trends of initial nursing education in China from 2006 to 2017 and to analyze related characteristics and issues. Design: A descriptive study with secondary data analysis. Methods: The numbers, educational-level composition and regional distribution (i.e., East, Central, West, and Northeast regions) of students recruited into initial nursing education programs from 2006 to 2017 were analyzed. Changes in the numbers of the nursing workforce from 2006 to 2020 were compared with the changes in education sector to facilitate an interpretation of the development trend of initial nursing education. Results: The number of recruits into initial nursing education programs has increased from 0.38 million in 2006 to 0.44 million in 2008, and maintained between 0.5 million and 0.54 million during 2009 to 2017. Students recruited to secondary diploma, advanced diploma, and baccalaureate degree programs accounted for 50.55% (71.46% in 2009), 39.36% and 10.09% of the total in 2017, respectively. There were 3.34 nurses per 1000 population in 2020, a substantial increase from 1.09 in 2006. The regional distribution of recruits was imbalanced, with more recruits per 1000 population in the West (0.49), Central (0.40), Northeast (0.34) and the least in the East (0.26) in 2017. The distribution of nurses was relatively balanced among the four regions. Conclusions: The development in initial nursing education in China is significant from 2006 to 2017. The education sector recruited and graduated about 0.5 million nursing students respectively per year in recent years. If simply considering the number of recruits, it could meet the workforce demands, however, to further upgrade nurses' educational preparation, the recruits into advanced diploma and baccalaureate degree programs need to be increased. A maldistribution of recruits among regions persists, while the distribution of nurses is relatively balanced. Multiple strategies should be adopted to achieve a balance between the supply and demand of nurses, with providing more higher-educated nurses in all regions across mainland China.